2011
DOI: 10.1002/jrs.2919
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman investigation of tin dioxide nanostructured material based on annealing effect

Abstract: Rutile-structured nanocrystalline tin dioxide (SnO 2 ) powder was synthesized by the chemical precipitation method using the precursor SnCl 2 • 5H 2 O. The SnO 2 powder was annealed at different temperatures, namely, 600, 800 and 1000 • C. Micro-Raman spectra were recorded for both the as-grown and annealed SnO 2 nanocrystalline samples. Micro-Raman spectral measurements on the SnO 2 nanoparticle show the first-order Raman modes A 1g (633 cm −1 ), E 1g (475 cm −1 ) and B 2g (775 cm −1 ), indicating that the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…According to some reports about CaSnO 3 and SrSnO 3 [36][37][38]48], the symmetric stretching vibrations of Sn-O and the symmetric vibrations of SnO 6 octahedra produce high intensity Raman peaks (Fig. 3(d)) and IR absorption bands (Fig.…”
Section: Raman and Ir Spectramentioning
confidence: 93%
See 1 more Smart Citation
“…According to some reports about CaSnO 3 and SrSnO 3 [36][37][38]48], the symmetric stretching vibrations of Sn-O and the symmetric vibrations of SnO 6 octahedra produce high intensity Raman peaks (Fig. 3(d)) and IR absorption bands (Fig.…”
Section: Raman and Ir Spectramentioning
confidence: 93%
“…CaSnO 3 exhibits a perovskite structure and isostructural with CaGeO 3 , SrSnO 3 and GdFeO 3 [33][34][35][36][37][38][39]. The structure itself is distorted through the tilting and distortion of SnO 6 octahedron.…”
Section: Description Of the Structure And Normal Mode Determinationmentioning
confidence: 99%
“…It is observed that the value of K SV is large compared with V, which explains the lack of major absorption change on addition of the quencher [24]. The radii of the quencher as determined by the Micro-Raman spectroscopic technique [19] is equal to 80 nm which is greater than that of the kinetic distance. This verifies that the quenching is not due to the sphere of action.…”
Section: Discussionmentioning
confidence: 94%
“…Then for about 5 hours in air it was annealed in a muffle furnace at 600˚C to enhance the crystallinity of SnO 2 NPs and the product appeared as white in color after the heat treatment. The particle size of the resultant product was found as 160 nm using micro Raman spectroscopic technique [19].…”
Section: Methodsmentioning
confidence: 99%
“…Supplementary bands appearing either in the regions of 350 cm -1 or 570 cm -1 have been cited. These bands have been linked to surface modes, [24,[28][29][30][31] oxygen vacancies [30,32] or crystalline interface disorder. [33,34] In our work, we cannot discuss any eventual bands related to SnO 2 in the 550-580 cm -1 region because the D 2 band of SiO 2 completely masks this part of the spectrum.…”
Section: Raman and Ft-raman Spectroscopymentioning
confidence: 99%